Food tourism around the world : development, management and markets - Hall, Colin Michael, 1961- (Amsterdam ; London : Elsevier Butterworth-Heinemann, 2004)
Food and wine are vital components of the tourism experience, and are increasingly being seen as prime travel motivators in their own right. Food Tourism Around The World: Development, Management and Markets offers a unique insight into this phenomenon, looking at the interrelationship between food, the tourism product and the tourist experience. Using international case studies and examples from Europe, North America, Australasia and Singapore, Food Tourism Around The World: Development, Management and Markets discusses the development, range and repurcussions of the food tourism phenomenon.
Publikace se zaměřuje na fenomén potravinového a gastronomického cestovního ruchu jako významné součásti současné turistické zkušenosti a stále důležitějšího motivačního faktoru cestování. Analyzuje vztah mezi místní gastronomií, turistickým produktem a prožitkem návštěvníků a věnuje se otázkám rozvoje, řízení a tržního uplatnění food tourismu. Na základě mezinárodních případových studií z Evropy, Severní Ameriky, Australasie a Singapuru kniha ukazuje ekonomické, kulturní i regionální dopady tohoto typu cestovního ruchu.
Obsahuje bibliografické odkazy a rejstřík
Keywords: cestovní ruch; gastronomický cestovní ruch; vinařská turistika; management cestovního ruchu; případové studie; sborníky; tourism; food tourism; wine tourism; tourism management; case studies